A cross-cultural study on odor-elicited life stage-associations. (February 2023) - Wendelin, Martin; Bauer, Andrea; Buchinger, Elisabeth; Danner, Lukas; Derndorfer, Eva; Thi Minh Hang, Vu; Hopfer, Helene; Wallner, Marlies; Jantathai, Srinual; Julius, Nina; Matullat, Imke; Majchrzak, Dorota; et al.
Graphical abstract: Highlights: Non-trained individuals from seven countries associated nine selected odors with four stages of life. Similarities but also differences in odor-elicited life stage-associations were found over the countries. Both age and gender affected odor-elicited life stage-associations. Abstract: Associative conceptualization plays an important role in how we perceive and interact with our environment. Particularly odor associations can be highly vivid and often long-lasting due to their close connection with our episodic memory and emotions. Based on the findings of a study conducted in Austria in 2017, this work was carried out to investigate odor-elicited life stage-associations (OELSA) in seven nations and to identify potential similarities and differences in conceptualizing odor impressions across these nations. A total of 1144 adults (aged 21–60) from Austria, Australia, Germany, Switzerland, Thailand, USA, and Vietnam participated in this study. Nine odors ( vanilla, orange, lemon, mint, coconut, basil, rose, anise, and hay ) were presented to the participants, and they were asked to answer questions about their spontaneous associations with life stages. The results indicate the existence of OELSA in all investigated nations. For example, vanilla was predominantly assigned to children in all nations, while hay was primarily assigned to elder people. While most of the investigated odors were most frequently associated with adults, some significant differences in OELSA were observed between the different nationalities. For instance, mint was more frequently associated with children by Australian participants compared to participants from all other nations, while coconut was more strongly associated with children by the Vietnamese participants compared to all other participants. The results of this study demonstrate the existence of consistent life stage-related associations elicited by certain odors across different nations and cultures and, at the same time points to differences in life stage-related association with certain odors between the nations. Since this work was not designed to identify the reasons for these differences, we can only make assumptions about the potential underlying causes for these behaviors.